Kaolin hemostatic material with anti-inflammatory function as well as preparation method and application thereof
The preparation of CeO2-loaded kaolin nanomaterials was performed through mechanochemical synthesis, which solved the problems of bleeding and inflammation control after debridement of diabetic foot, achieved the synergistic effect of hemostasis and anti-inflammatory, and improved the safety and production feasibility of materials.
Patent Information
- Application Number
- CN202411366995.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The prior art is difficult to effectively control bleeding and inflammatory reactions after debridement of diabetic foot. Traditional hemostatic materials may not be sufficient to meet the needs of anticoagulant users. There is a problem of using toxic solvents and stabilizers in the synthetic method, which affects the material. Biosafety and product purity.
By using mechanochemical synthesis method, kaolin nanomaterials loaded with cerium chloride, sodium carbonate and sodium chloride were mixed and ball milled to obtain CeO2-loaded kaolin nanomaterials, achieving synergistic effects of anti-inflammatory and hemostasis.
Effective hemostasis and anti-inflammatory effects after debridement of diabetic foot is achieved, avoiding the risk of using toxic solvents in traditional methods, and the nanoparticles of the material are highly consistent in size and shape, meeting the needs of large-scale industrial production.
Smart Images

Figure CN119455057A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hemostatic materials, and in particular to a kaolin hemostatic material with anti-inflammatory function and a preparation method and application thereof. Background Art
[0002] In the treatment of diabetic foot, debridement is a necessary step to remove necrotic tissue (including bones and abscesses). However, the common vascular lesions in diabetic patients require them to receive anticoagulant therapy to prevent cardiovascular events, which also increases the risk of postoperative bleeding. Therefore, after debridement, not only effective hemostatic measures are needed, but also the control of inflammatory response to reduce the risk of infection and promote wound healing.
[0003] At present, the commonly used hemostatic materials in clinical practice are mainly sterilized gauze, but for diabetic patients who use anticoagulants for a long time, these traditional methods may not be enough to effectively control bleeding and may prolong the patient's hospitalization time. In order to improve the effect of diabetic wound treatment, it is crucial to find materials with better hemostatic and anti-inflammatory effects.
[0004] Kaolin (K), as a natural mineral, has shown great potential in the field of hemostasis due to its excellent physical and chemical properties and biocompatibility. Studies have shown that kaolin dressings have significant hemostatic effects in trauma and percutaneous vascular intervention. The invention patent [CN 117462732 A] focuses on improving the hemostatic effect of kaolin and solving the problems of easy agglomeration and pulverization; the invention patent [CN 109481731 B] uses nano-oxides to give kaolin hemostatic materials antibacterial properties, allowing the material to exert synergistic hemostatic and antibacterial effects. The invention patent [CN 116177587 A] invented a mesoporous CeO2 nanocomposite material and confirmed that it has strong antioxidant capacity. However, there is no kaolin-based material specifically for the synergistic hemostasis and anti-inflammatory effects after debridement of diabetic foot.
[0005] In addition, existing synthesis methods often use toxic solvents or reagents, such as NaOH and H2SO4, which may remain on the surface of nanoparticles, leading to potential adverse biological reactions. The use of external stabilizers or capping agents may also reduce the biosafety of the materials. In the large-scale production process, there is also the problem of difficulty in controlling the consistency of nanoparticle size and shape, which makes it difficult to ensure product purity and consistency. Summary of the invention
[0006] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a kaolin hemostatic material with anti-inflammatory function and a preparation method and application thereof.
[0007] The invention discloses a kaolin hemostatic material with anti-inflammatory function, comprising kaolin loaded with CeO2 nanoparticles.
[0008] A method for preparing the kaolin hemostatic material with anti-inflammatory function as mentioned above comprises mixing kaolin with cerium chloride, sodium carbonate and sodium chloride in a certain mass ratio and then ball milling to obtain a precursor, and calcining the precursor to obtain the kaolin hemostatic material with anti-inflammatory function.
[0009] Furthermore, the mass ratio of kaolin to cerium chloride, sodium carbonate and sodium chloride is 1:0.2 to 2.35:1.25:1.15.
[0010] Furthermore, in step S2, the calcination temperature is 200°C-800°C, and the calcination time is 0.5-4h.
[0011] Furthermore, in step S2, the calcination heating rate is 4-6°C / min.
[0012] Furthermore, the ball-to-material ratio of the ball mill is 130:7.2-10.7, the rotation speed is 400-560rpm, and the time is 0.5-4h.
[0013] Furthermore, the ball milling container is a 100 mL zircon jar; the medium is zircon balls with diameters of 10 mm, 8 mm, and 5 mm, and the ratio is 2:3:5; the ball milling uses a planetary ball mill, which synthesizes the material according to the ball milling strategy of forward rotation for 30 minutes, reverse rotation for 30 minutes, and stopping for 5 minutes before the next cycle.
[0014] Furthermore, the kaolin, cerium chloride, sodium carbonate and sodium chloride were dried before ball milling; the drying temperature was 180° C. and the drying time was 13 h.
[0015] Furthermore, after the precursor is calcined, it is centrifugally washed 2-8 times and then dried at 45°C.
[0016] An application of the kaolin hemostatic material with anti-inflammatory function as described above is characterized in that it is used as a hemostatic material after debridement of diabetic foot.
[0017] The present invention adopts kaolinite, which is inexpensive and abundant in reserves, as a raw material, selects conventional CeO2 raw materials, and prepares kaolin-based nanomaterials loaded with CeO2 by a mechanochemical synthesis method, thereby preparing CeO2 / K nanomaterials with high consistency in nanoparticle size and shape and synergistic anti-inflammatory and hemostatic activities. In the present invention, kaolinite provides hemostasis and stabilizes CeO2 nanoparticles, and CeO2 has catalytic properties to achieve anti-inflammatory effects, thereby achieving synergistic anti-inflammatory and hemostatic effects. In addition, the present invention has a short experimental cycle, a simple operating process, and can also achieve green production and meet the needs of large-scale industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1Schematic diagram of the synthesis process of CeO2 / K;
[0019] Figure 2 is the X-ray diffraction pattern of Kaol and CeO2 / K;
[0020] Figure 3 is the SEM image of Kaol;
[0021] Figure 4 This is the scanning electron microscope image of CeO2 / K;
[0022] Figure 5 BCI index diagram of CeO2 / K at 200 and 800℃;
[0023] Figure 6 BCI index diagram of Kaol and CeO2 / K;
[0024] Figure 7 The in vitro nanozyme activity diagram of Kaol and CeO2 / K;
[0025] Figure 8 This is a graph showing the changes in TNF-α levels in LPS-induced macrophages after the action of CeO2 / K. DETAILED DESCRIPTION
[0026] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0027] The preparation method of kaolin hemostatic material with anti-inflammatory function is as follows:
[0028] First, weigh 2.5g Na2CO3, 2.3g NaCl, 4.7g anhydrous CeCl3 and 2g kaolinite, wherein NaCO3, NaCl and anhydrous CeCl3 are dried overnight at high temperature; then maintain a certain ball-to-material ratio, turn the planetary ball mill at a speed of 560rpm, ball mill for a period of time, and the mechanochemical product is a kaolinite-based nanomaterial precursor. Then place the precursor in a muffle furnace and roast it at a certain temperature for a period of time. Finally, wash the product, stir with deionized water, wash the product, then dehydrate it, and finally dry it at 45°C for 24h to obtain the final product, i.e., CeO2-loaded kaolin nanomaterial (CeO2 / K).
[0029] Example 1
[0030] In this embodiment, CeO2 / K was prepared according to the above method with different material ratios (1:0.25-2.35:1.25:1.15).
[0031] First, weigh 2.5g Na2CO3, 2.3g NaCl, 0.47, 1.41, 2.342, 3.279, 4.7g anhydrous CeCl3 and 2g kaolinite, wherein NaCO3, NaCl and anhydrous CeCl3 were dried at high temperature overnight, and the raw materials were mechanochemically synthesized using a planetary ball mill at a ball-to-material ratio of 130:10.7 and a speed of 560rpm for 4h. After the ball milling, the raw materials were placed in a muffle furnace at a heating rate of 5° / min and roasted at 400℃ for 1h. After the roasting, the powder material was transferred to a 50mL centrifuge tube and washed by centrifugation at 8000r / min for 6 times. Finally, the mixture was kept at 45℃ for 720min and dried to obtain CeO2 / K with different material ratios.
[0032] Example 2
[0033] In this example, CeO2 / K was prepared according to the above method with different ball milling times (0.5 to 4 h).
[0034] First, weigh 2.5g Na2CO3, 2.3g NaCl, 4.7g anhydrous CeCl3 and 2g kaolinite, wherein NaCO3, NaCl and anhydrous CeCl3 were dried at high temperature overnight, and the raw materials were mechanochemically synthesized using a planetary ball mill at a ball-to-material ratio of 130:10.7 and a speed of 560rpm for 0.5h, 1h, 2h, 3h and 4h respectively. After the ball milling, the raw materials were placed in a muffle furnace at a heating rate of 5° / min and roasted at 400℃ for 1h. After the roasting, the powder material was transferred to a 50mL centrifuge tube and washed by centrifugation at 8000r / min for 6 times. Finally, the mixture was kept at 45℃ for 720min and dried to obtain CeO2 / K.
[0035] Example 3
[0036] In this embodiment, CeO2 / K was prepared according to the above method with different ball-to-material ratios (130:7.2, 8, 8.8, 10.7 and 12.6).
[0037] First, weigh 2.5g Na2CO3, 2.3g NaCl, 4.7g anhydrous CeCl3 and 2g kaolinite, wherein NaCO3, NaCl and anhydrous CeCl3 were dried at high temperature overnight, and the raw materials were ball milled for 4h at 560rpm using a planetary ball mill, and the ball to material ratio was 130:7.2, 8, 8.8, 10.7 and 12.6 respectively. After the ball milling, it was placed in a muffle furnace at a heating rate of 5° / min and calcined at 400℃ for 1h. After the calcination, the powder was transferred to a 50mL centrifuge tube and washed by centrifugation at 8000r / min for 6 times. Finally, it was kept at 45℃ for 720min and dried to obtain CeO2 / K.
[0038] Example 4
[0039] In this embodiment, CeO2 / K was prepared according to the above method at different calcination temperatures (200-800°C).
[0040] First, weigh 2.5g Na2CO3, 2.3g NaCl, 4.7g anhydrous CeCl3 and 2g kaolinite, wherein NaCO3, NaCl and anhydrous CeCl3 were dried at high temperature overnight, and the raw materials were ball-milled for 4h using a planetary ball mill at a ball-to-material ratio of 130:10.7 and a rotation speed of 560rpm. After the ball milling, the raw materials were placed in a muffle furnace at a heating rate of 5° / min and calcined at 200℃, 300℃, 400℃, 500℃ and 800℃ for 1h. After the calcination, the powder was transferred to a 50mL centrifuge tube and washed by centrifugation at 8000r / min for 6 times. Finally, the powder was kept at 45℃ for 720min and dried to obtain CeO2 / K.
[0041] Example 5
[0042] In this example, CeO2 / K was prepared according to the above method with different calcination times (0.5-4h).
[0043] First, weigh 2.5g Na2CO3, 2.3g NaCl, 4.7g anhydrous CeCl3 and 2g kaolinite, wherein NaCO3, NaCl and anhydrous CeCl3 were dried at high temperature overnight, and the raw materials were ball-milled for 4h using a planetary ball mill at a ball-to-material ratio of 130:10.7 and a rotation speed of 560rpm. After the ball milling, the raw materials were placed in a muffle furnace at a heating rate of 5° / min and calcined at 400℃ for 0.5h, 1h, 2h, 3h and 4h respectively. After the calcination, the powder was transferred to a 50mL centrifuge tube and washed by centrifugation at 8000r / min for 6 times. Finally, the powder was kept at 45℃ for 720min and dried to obtain CeO2 / K.
[0044] Example 6
[0045] In this embodiment, CeO2 / K was prepared according to the above method by centrifugal dehydration for 2, 4, 6, and 8 times to remove impurities that were not successfully synthesized.
[0046] First, weigh 2.5g Na2CO3, 2.3g NaCl, 4.7g anhydrous CeCl3 and 2g kaolinite, wherein NaCO3, NaCl and anhydrous CeCl3 were dried at high temperature overnight, and the raw materials were ball-milled for 4h using a planetary ball mill at a ball-to-material ratio of 130:10.7 and a rotation speed of 560rpm. After the ball milling, the raw materials were placed in a muffle furnace at a heating rate of 5° / min and roasted at 400℃ for 1h. After the roasting, the powder was transferred to a 50mL centrifuge tube and centrifuged and washed at 8000r / min for 2, 4, 6, and 8 times. Finally, the powder was kept at 45℃ for 720min and dried to obtain CeO2 / K.
[0047] Figure 1 This is a schematic diagram of the synthesis process of CeO2 / K. It can be seen from the figure that the synthesis process of CeO2 / K is simple and green.
[0048] X-ray diffraction analysis was performed on CeO2 / K prepared in Example 1-6. The results showed that the CeO2 grains were continuously refined with the increase of ball milling time and the decrease of ball to material ratio. This is because the powder refinement speed in the ball mill is accelerated and the product grains are continuously reduced with the increase of ball milling time and the decrease of ball to material ratio. At the same time, the change of roasting temperature and roasting time will cause the kaolinite crystal form to change, and the increase of temperature and time will promote the CeO2 grains to be more complete and its grain size to increase. In addition, the number of dehydration times affects the residual diluent NaCl. With the increase of dehydration times, the characteristic absorption peak of NaCl gradually decreases until it disappears completely at 6 times.
[0049] Figure 2 The X-ray diffraction pattern of CeO2 / K synthesized after six dehydration cycles in Example 6 is shown in Figure 2 The diffraction peaks 2θ observed in the experiment are 28.55°, 33.08°, 47.48°, 56.34°, 59.08°, 69.41°, 76.70° and 79.07°, which correspond to cubic fluorite CeO2 with space group Fm3m (PDF#01-075-8371). The diffraction peaks 2θ of 12.38°, 19.85°, 20.33°, 21.25°, 23.14° and 24.90° correspond to Kaol (PDF#01-080-0886), which confirms that the synthesized product is a composite material of kaolinite and CeO2. In the CeO2 / K composite, the kaolinite lattice is not destroyed, and the kaolinite in the composite material maintains its original crystalline structure.
[0050] Figure 3 This is the scanning electron microscope image of Kaol. The microscopic morphology and structure of Kaol were analyzed by SEM. Kaol mainly presents a two-dimensional lamellar structure with a smooth surface and clear boundaries.
[0051] Figure 4 This is the scanning electron microscope image of CeO2 / K synthesized after dehydration 6 times in Example 6. It can be clearly observed that CeO2 is successfully anchored on the surface of kaolinite, the CeO2 particles are aggregates with small spherical particles, and the kaolinite is completely covered by CeO2 particles.
[0052] The coagulation experiment was conducted on CeO2 / K prepared in Example 1 to Example 6. It was found that the longer the ball milling time, the worse the coagulation effect after kaolinite turned to amorphization, but the ball-to-material ratio and the number of dehydration times had little effect on the coagulation effect. The calcination temperature and time also affect the coagulation effect of the material. As the temperature and time reach 800°C and 1h, the coagulation effect of the material is significantly reduced, and the increase in temperature shows a reverse coagulation effect. However, too low a temperature will affect the generation of CeO2 particles. Therefore, taking into account the synergistic effects of anti-inflammatory and hemostasis and according to the actual product needs, the ball milling time, calcination temperature and calcination time can be comprehensively optimized.
[0053] Figure 5 The BCI index diagrams are prepared after CeO2 / K materials were calcined at 200℃ and 800℃, respectively. Effective hemostasis is the key to hemostatic materials. The lower the blood clotting index (BCI), the stronger the hemostatic ability. In the CeO2 / K coagulation experiment, it was found that the BCI index of the material at 200℃ decreased from 95.57±0.85% to 44.77±0.36%, and the BCI index of the material at 800℃ increased to 81.23±1.96%. This result confirms that temperature actually affects the coagulation effect of the material. The higher the temperature, the higher the BCI, indicating that high temperature deteriorates the hemostatic performance of the material. Therefore, the calcination temperature should be selected reasonably.
[0054] Figure 6 The BCI index graph of CeO2 / K prepared after 6 dehydration times in Kaol and Example 5. In the CeO2 / K coagulation experiment, it was found that the BCI index decreased from 105.54±0.9% to 69.61±1.16%. It is worth noting that CeO2 cannot effectively stop bleeding, but will deteriorate the hemostatic effect. The use of kaolinite to load CeO2 improves the hemostatic performance of the material.
[0055] Figure 7The in vitro nanozyme activity diagram of CeO2 / K prepared after dehydration 6 times in Kaol and Example 5. Removal of ROS is the main factor in the inhibition of inflammatory diseases by anti-inflammatory materials. Reducing excessive ROS can prevent the further development of the disease or promote the regeneration of damaged inflammatory tissues. Peroxidase (CAT) can remove superoxide anions and tandem hydrogen peroxide to produce molecular oxygen and slow down the occurrence of inflammation. From the in vitro CAT nanozyme activity diagram of Kaol and CeO2 / K, it can be seen that Kaol does not have CAT activity, but the CAT enzyme activity increases after loading CeO2, and the oxygen production capacity is further improved. It proves that CeO2 / K has in vitro CAT enzyme activity.
[0056] Figure 8 This is a graph showing the changes in TNF-α levels in LPS-induced macrophages after CeO2 / K treatment. In order to further understand the anti-inflammatory mechanism of CeO2 / K, the levels of related cytokines (α-tumor necrosis factor, TNF-α) in inflammatory tissues were quantitatively analyzed by enzyme-linked immunosorbent assay (ELISA). The results showed that CeO2 / K could effectively downregulate the proinflammatory cytokine TNF-α and inhibit the inflammatory death of macrophages in the inflammation-induced model, thereby protecting the cells from H2O2-induced oxidative damage.
[0057] For matters not mentioned above, the prior art applies.
[0058] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A kaolin hemostatic material with anti-inflammatory function, characterized in that: It includes kaolin loaded with CeO2 nanoparticles.
2. A method for preparing the kaolin hemostatic material with anti-inflammatory function as claimed in claim 1, characterized in that: Kaolin is mixed with cerium chloride, sodium carbonate and sodium chloride in a certain mass ratio and then ball-milled to obtain a precursor, and the precursor is calcined to obtain a kaolin hemostatic material with anti-inflammatory function.
3. The preparation method according to claim 2, characterized in that: The mass ratio of kaolin to cerium chloride, sodium carbonate and sodium chloride is 1:0.2-2.35:1.25:1.
15.
4. The preparation method according to claim 2, characterized in that: The calcination temperature is 200°C-800°C and the time is 0.5-4h.
5. The preparation method according to claim 2, characterized in that: The calcination heating rate is 4-6℃ / min.
6. The preparation method according to claim 2, characterized in that: The ball-to-material ratio of the ball mill is 130:7.2-10.7, the rotation speed is 400-560rpm, and the time is 0.5-4h.
7. The preparation method according to claim 2, characterized in that: The ball milling container is a 100mL zircon jar; the medium is zircon balls with diameters of 10mm, 8mm, and 5mm, and the ratio is 2:3:5; the ball milling uses a planetary ball mill, which synthesizes the material according to the ball milling strategy of forward rotation for 30min, reverse rotation for 30min, and stopping for 5min before the next cycle.
8. The preparation method according to claim 2, characterized in that: Before ball milling, kaolin, cerium chloride, sodium carbonate and sodium chloride were dried at 180°C for 13 hours.
9. The preparation method according to claim 2, characterized in that: After the precursor is calcined, it is centrifugally washed 2-8 times and then dried at 45°C.
10. An application of the kaolin hemostatic material with anti-inflammatory function as claimed in claim 1, characterized in that: Used as a hemostatic material after debridement of diabetic foot.
Citation Information
Patent Citations
Hemostasis composition based on kaolin and quercetin, styptic powder and preparing method of styptic powder
CN105412147A
Nano ZnO / kaolin composite antibacterial material and preparation method thereof
CN115226723A
Kaolin-based composite styptic powder and preparation method thereof
CN118340933A
A composition based on cerium dioxide nanoparticles and brown algae polysaccharides for the treatment of wounds
RU2018101481A
Cerium oxide nanoparticles and associated methods for promoting wound healing
US20130195927A1
Cited By
Silicon carbon ore-based multifunctional hemostatic material and preparation method thereof
CN121102552A